Effect of Tai Chi Softball on Health-Related Outcomes in Elderly Men - XiaoDong Cheng; Naichun Ji (American Journal of Men's Health)
This study aimed to investigate the effects of Tai Chi Softball (TCSB) training on the physical health of older men, with a focus on improvements in muscle strength, flexibility, balance, and blood lipid profiles. A 12-week randomized controlled trial was conducted, recruiting 140 men aged 55–65 years. Participants were randomly assigned to either a Tai Chi Softball group (TCSBG, N  = 70) or a control group (CG, N  = 70). The TCSBG engaged in TCSB training sessions 4 to 5 times per week, with each session lasting 70 to 90 min, while the CG maintained their usual daily routines without any additional interventions. Measurements were taken before and after the intervention and included waist-to-hip ratio (WHR), handgrip strength (HS), sit-and-reach (SAR), single-leg stance (SLS), vital capacity (VC), heart rate, systolic blood pressure (SBP), diastolic blood pressure (DBP), total cholesterol (TC), triglycerides (TG), low-density lipoprotein cholesterol (LDL-C), and high-density lipoprotein cholesterol. The results revealed that after 12 weeks of TCSB training, participants in the TCSBG showed significant improvements ( p  < .05) in HS, SAR, and SLS, indicating enhanced muscle strength, flexibility, and balance, respectively. The VC also increased significantly, while both SBP and DBP decreased notably ( p  < .05). Moreover, significant reductions were observed in TC, TG, and LDL-C levels p  < .05). In conclusion, TCSB training demonstrated efficacy in improving muscle strength, flexibility, balance, cardiorespiratory fitness, and blood lipid profiles in older men. These findings suggest that TCSB training can mitigate age-related declines in physical function and reduce cardiovascular risk in older men.